(untitled) (Journal of Tikapur Multiple Campus, 2026)
Pesticides are essential for safeguarding crops both in the field and during storage purpose in Nepal. This study investigated vegetable growers’ purchasing habits and the factors that influence their purchasing behavior among vegetable farmers in Ghorahi, Dang. A semi-structured interview schedule was used to interview 92 farmers who were chosen by simple random sampling. The results indicated majority of the vegetable growers i.e. 90.2% purchased pesticide from Agro-vet stores or pesticide retailers. Among the pesticides, the most often used pesticide was insecticide, which was followed by herbicides, fungicides, rodenticides, and nematicides. The most significant issue of farmers regarding pesticide purchase was lack of knowledge of farmers in choosing the right pesticides for their target pests, followed by the high cost of insecticides and the absence of sustainable substitutes like bio-pesticides. Retailer recommendations, prior experience, cost, simplicity of use, and brand trust were important factors affecting purchase decisions. Improving farmers’ purchasing decisions requires targeted training and awareness initiatives, cooperation between farmers, retailers, cooperatives, and governmental organizations, as well as suitable guidance.